2013
DOI: 10.1080/09593330.2013.832336
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal from slaughterhouse wastewater through partial nitrification followed by denitrification in intermittently aerated sequencing batch reactors at 11°C

Abstract: This study is aimed to examine the removal of nitrogen from high strength slaughterhouse wastewater at 11 degreeC via partial nitrification followed by denitrification (PND), using the intermittently aerated sequencing batch reactor (IASBR) technology. The slaughterhouse wastewater contained chemical oxygen demand (COD) of 6068 mg/L, total nitrogen (TN) of 571 mg/L, total phosphorus (TP) of 51 mg/L and suspended solids of 1.8 g/L, on average. The laboratory-scale IASBR reactors had a working volume of 8 L and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
6
25
1
1
Order By: Relevance
“…Kinetic coefficients were also determined. Pan et al (2014) evaluated the removal of TN from SWW at low temperatures of up to 11 C through partial nitrificationedenitrification by means of an 8-L SBR. The influent concentration of the SWW contained COD, TN, TP, and TSS concentrations of 6068, 571, 51, 1800 mg/L, respectively.…”
Section: Aerobic Sequencing Batch Reactormentioning
confidence: 99%
“…Kinetic coefficients were also determined. Pan et al (2014) evaluated the removal of TN from SWW at low temperatures of up to 11 C through partial nitrificationedenitrification by means of an 8-L SBR. The influent concentration of the SWW contained COD, TN, TP, and TSS concentrations of 6068, 571, 51, 1800 mg/L, respectively.…”
Section: Aerobic Sequencing Batch Reactormentioning
confidence: 99%
“…Meyer et al [5] noted that nitrification and denitrification would be incompletely coupled to each other due to nonformation of aerobic/anoxic zones within the microbial aggregates, resulting in buildup of NO x − in the reactor. In comparison with the conventional nitrification and denitrification of abattoir wastewater, several advantages of a shortcut nitrogen removal method via nitrite, through partial nitrification followed by denitrification (PND), have been reported recently [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SND processes are characterized by increased nitrogen removal rates and decreased reaction time. The key point in the PND process is maintaining the production rate of nitrite by ammonium oxidizing bacteria (AOB) higher than the production rate of nitrate by nitrite oxidizing bacteria (NOB) so that nitrite accumulation can be achieved [6]. In contrast, maintenance of a population balance is not necessary in SND as the two reactions (nitrification and denitrification) proceed under identical reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the third stage the aerated wastewater is given a time for TSS to settle and finally the supernatant is discharged in the fourth stage. Although some studies have demonstrated high nutrients and COD removal using aerobic SBR [54,55], judging from the mixing and fluid transport requirements one can infer that this process is an energy intensive one.…”
Section: Aerobic Treatmentmentioning
confidence: 99%